Syrian Refugees and Human Capital Accumulation of Native Children in Turkey - Selcen Çakır; Elif Erbay; Murat G. Kirdar (Institute of Labor Economics (IZA), 2021)
Turkey hosts the highest number of refugees in the world. The arrival of Syrian refugees has significantly changed the relative abundance of different skill groups in Turkey and the labor market conditions. This paper examines how this massive refugee influx affects native working-age children's school enrollment and employment outcomes using a difference-indifferences IV methodology. We find that employment of both boys and girls falls substantially, but a large fraction of this fall stems from the transition of children who used to combine school and work into school only. School enrollment increases only for boys, and this is stronger for boys with more educated parents. The incidence of being neither in employment nor in education or training (NEET) increases among girls, particularly for those with less-educated parents, but not among boys. In fact, the NEET incidence drops for boys with more-educated parents.
Keywords: I25; J61; 330; syrian refugees; school enrollment; employment; child work; education; NEET; Turkey